I believe it would be multiplied by -0.5 or -1/2.
Answer:
a. (-3, 2).
b. √65
c. (x + 3)^2 + (y - 2)^2 = 65
Step-by-step explanation:
a. The center is the midpoint of the diameter PQ.
= (-10+4)/2, (-2+6)/2
= (-3, 2).
b. The radius is the distance from the center to a point on the circle.
Take the point (4, 6):
The radius = √((-3-4)^2 + (2-6)^2)
= √65.
c. The equation of the circle is:
Using the standard form
(x - h)^2 + (y - k)^2 = r^2 where (h, k) is the center and r = the radius:
it is (x - (-3)^2 + (y - 2) = 65
= (x + 3)^2 + (y - 2)^2 = 65.
Answer:
$25
Step-by-step explanation:
i have an odd method of solving these types of equations
25x=100
x=4
340/4 = 85
85 x 3 = 255
I believe the answer is b
Answer:
(0,-3)
Step-by-step explanation:
You can just graph it and find the center.
Please put me as brainliest. Thank you.